Predictors of Breast Discomfort among Women Initiating Menopausal Hormone Therapy - Crandall, Carolyn J. (2010)
OBJECTIVE: To study the determinants of breast discomfort among postmenopausal women initiating menopausal hormone therapy (HT). METHODS: We analyzed questionnaire, anthropometric, and serum estrone data from the Postmenopausal Estrogen/Progestin Interventions Trial (PEPI), a randomized trial comparing placebo, conjugated equine estrogen (CEE) alone, or CEE with a progestogen (continuous or cyclical medroxyprogesterone acetate or cyclical micronized progesterone) among postmenopausal women. HT users could join PEPI after stopping HT for 2 months. We modeled the relation between smoking, body weight, alcohol consumption, age, quitting HT to join PEPI, physical activity and alpha-tocopherol consumption and new-onset breast discomfort at 12-month follow-up among 662 participants without baseline breast discomfort. RESULTS: The associations of new-onset breast discomfort with weight and with strenuous exercise varied by treatment assignment. Among women assigned to CEE + progestogen, strenuous exercise was associated with a 49% lower odds of new-onset breast discomfort (OR 0.51, 95% CI 0.29–0.89, P = 0.02), whereas among women assigned to placebo or CEE alone, strenuous exercise was not significantly associated with new-onset breast discomfort. Surprisingly, among women taking CEE alone, each kilogram higher weight was associated with 6% lower odds of new-onset breast discomfort (P=0.04), whereas among women taking placebo, the association was in the opposite direction (P=0.04). Adjustment for estrone level had neglible effects on odds ratios. Alpha-tocopherol intake, age, smoking, and alcohol intake were not significantly associated with new-onset breast discomfort in adjusted analyses. CONCLUSION: Strenuous exercise and higher body weight may decrease the odds of new-onset breast discomfort among postmenopausal women initiating HT.